Business model identification in the selected value chains in the Northwest of Tunisia: Case of Kef and Siliana - Dhehibi, Boubaker; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Souissi, Asma; Majri, Rihab; Frija, Aymen; Ouerghemmi, Hassen; Alary, Veronique; Ouji, Mourad; Idoudi, Zied; Rudiger, Udo; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2022)
The report describes the approach used to co-identify potential Business Models through the integration of HLPE’s agroecological principles in a variety of Value chains co-selected in the Agroecological Living Landscape ‘Kef-Siliana Transect’, Northwest Tunisia.